Contemporary catalysis : science, technology, and applications - Kamer, Paul; Vogt, Dieter; Thybaut, Joris (Royal Society of Chemistry, 2016)
Covering the basic principles, this book presents aspects of homogeneous, heterogeneous, organo-, bio- and computational catalysis. It discusses catalyst preparation, catalyst characterisation and reactor engineering and explores recent developments in the understanding of catalytic mechanism, such as operando spectroscopy.
Keywords: Catalysis.; elektronické knihy; electronic books